(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Annadrava shoola is one of the diseases of the alimentary canal in which there is colic occurs after digestion, during digestion or at any time and Patient feels relief after vomiting. It can be said gastric ulcer on the basis of its signs and symptoms. Gastric ulcers are most commonly located on the lesser curvature, whereas duodenal ulcers are most common at the duodenal bulb. The ulcer is round to oval with a smooth base. Acute ulcers have regular borders, while chronic ulcers have elevated borders with inflammation. An ulcer extends beyond the muscularis mucosa. Ayurveda encourages lifestyle interventions and natural therapies to regain a balance between the body, mind and the environment. In this paper, a case study on Annadrava shoola has been explained. A female patient of 42 years of age came to the Kayachikitsa OPD (OPD REG.no-6836) Government Ayurvedic College and Hospital, Patna-03 having complain of pain and burning sensation in abdomen for 5 months as well as irregular bowel evacuation (>3episode) in the last 3 months. The nature of pain was gradual on onset and burning type and exaggerated after meal. On the basis of history of the patient and endoscopy report, he was diagnosed as gastric ulcer and pan gastritis. We have done the Shamana Chikitsa for the patient. In Shamana Chikitsa was done with combinations of Sutashekhar Ras, Tab Aciloss and Shatavari Churna for one month. Endoscopy was repeated after one and half months of treatment. Report showed only that the treatment cured the Annadrava shoola (gastric ulcer) of the patient. So, there is hope in Ayurveda for the treatment of Annadrava shoola.